2017
DOI: 10.1212/wnl.0000000000003451
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic nucleus deep brain stimulation in isolated dystonia

Abstract: This study provides Class IV evidence that STN DBS decreases long-term dystonia severity in patients with medically refractory isolated dystonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 35 publications
4
65
4
1
Order By: Relevance
“…Pain is known to be one of the major determinants of HRQoL [2,74]. Bodily pain of SF-36 showed significant improvement in most studies [4,5,10,31,38,[40][41][42][43]45,47,73], which was consistent with the outcomes assessed with the scales specific to pain problems [5,34,38,39,75,76]. The general health scale of the SF-36 also significantly improved, suggesting that the patients' overall life satisfaction improved after DBS surgery [4,5,31,[41][42][43]45,72].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Pain is known to be one of the major determinants of HRQoL [2,74]. Bodily pain of SF-36 showed significant improvement in most studies [4,5,10,31,38,[40][41][42][43]45,47,73], which was consistent with the outcomes assessed with the scales specific to pain problems [5,34,38,39,75,76]. The general health scale of the SF-36 also significantly improved, suggesting that the patients' overall life satisfaction improved after DBS surgery [4,5,31,[41][42][43]45,72].…”
Section: Discussionsupporting
confidence: 68%
“…Most studies reported motor improvement according to the BFMDRS-M after bilateral STN DBS with a range between 40% and 80% similar to the outcomes of GPi DBS [40][41][42][43][44][45][46]. In a prospective study on 20 isolated dystonia patients with prominent cervical involvement, dystonia symptoms improved at 3 years by 70% and 67% according to BFMDRS-M and TWSTRS, respectively [40].…”
Section: Stn Dbsmentioning
confidence: 88%
See 1 more Smart Citation
“…The subthalamic nucleus (STN) has recently been proposed as a potential DBS target, alternative to GPi in patients with dystonia. A 3‐year follow‐up study provided class IV evidence that STN DBS decreases long‐term severity in patients with medically refractory isolated dystonia .…”
Section: Treatment/managementmentioning
confidence: 99%
“…Ostrem et al 3 found STN DBS improved CD symptoms by greater than 50% when followed for 36 months after surgery; however, the range of clinical improvement was wide (30%–80%) and the underlying physiological changes were not examined.…”
Section: Introductionmentioning
confidence: 99%